2012
DOI: 10.5194/bg-9-1183-2012
|View full text |Cite
|
Sign up to set email alerts
|

Coupled CO<sub>2</sub> and O<sub>2</sub>-driven compromises to marine life in summer along the Chilean sector of the Humboldt Current System

Abstract: Abstract. Carbon dioxide and coupled CO 2 and O 2 -driven compromises to marine life were examined along the Chilean sector of the Humboldt Current System, a particularly vulnerable hypoxic and upwelling area, applying the Respiration index (RI = log 10 pO 2 pCO 2 ) and the pH-dependent aragonite saturation ( ) to delineate the water masses where aerobic and calcifying organisms are stressed. As expected, there was a strong negative relationship between oxygen concentration and pH or pCO 2 in the studied area,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 47 publications
1
34
0
Order By: Relevance
“…~42° S) up to Ecuador and the Galapagos Islands near the Equator (~5° N), and is one of the most productive marine ecosystems in the world 38 . This system, and particularly the coastal region off Chile, is characterized by large spatial-temporal heterogeneity in p CO2 conditions 39,40 , and is an area in which the effects of low pH/high p CO2 conditions can already be seen (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…~42° S) up to Ecuador and the Galapagos Islands near the Equator (~5° N), and is one of the most productive marine ecosystems in the world 38 . This system, and particularly the coastal region off Chile, is characterized by large spatial-temporal heterogeneity in p CO2 conditions 39,40 , and is an area in which the effects of low pH/high p CO2 conditions can already be seen (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…The only other known study that tested the effects of environmental pH on squid-embryo statolith geochemistry found that only 65 Zn significantly differed from an elemental suite that included 110m Ag, 109 Cd, 57 Co, 203 Hg and 54 Mn [49]. Evidence that environmental tracers in squid statoliths can track seawater pH and [O 2 ] is especially useful, because uranium has been shown to be promising for understanding squid life history, migrations and habitat use [88,90,91].…”
Section: Discussionmentioning
confidence: 99%
“…Low pH/high pCO 2 and low [O 2 ] (hereafter referred to as "low pHOx") can cause species-specific negative effects in isolation or in tandem, and the magnitude of each of these effects is likely to be habitat specific [65,66]. We conducted experiments to investigate whether statolith geochemistry can reveal squid exposure to low pHOx, low [O 2 ] only and/or low pH/high pCO 2 only (hereafter, referred to as "low pH") during benthic encapsulated stages.…”
mentioning
confidence: 99%
“…The combined mechanisms of global CO 2 (and f CO 2 ) increase and more local deoxygenation (and f O 2 decrease) have just begun to be addressed (e.g., Paulmier et al, 2011;Pörtner et al, 2011;Gruber, 2011;Mayol et al, 2012;Brewer and Peltzer, 2009) and need to be further investigated. Surprisingly, there is a lack of studies that project the combined evolution of these variables under global warming and anthropogenic carbon emissions using fully coupled Earth System Models.…”
Section: Cocco Et Al: Oxygen and Indicators Of Stress In Multi-momentioning
confidence: 99%
“…Recently, observational studies focused on upwelling regions (Mayol et al, 2012;Paulmier et al, 2011), typical low-O 2 -high-CO 2 areas of particular vulnerability, where elevated f CO 2 levels represent a key threat connecting aerobic stress and calcification challenges. However, f CO 2 and CO 2 are not state variables in ocean biogeochemical models and coupled Earth System Models, and their distribution below the surface layer has been studied poorly.…”
Section: Cocco Et Al: Oxygen and Indicators Of Stress In Multi-momentioning
confidence: 99%